Cat’s tracker and health monitor - Sekeri, Suhairawani; Masek, Alias; Rudi, Mizan Adilliah (Penerbit UTHM, 2020)
Most people get pets for companionship, but tedious to take care, especially cat. Previous research suggests that having a pet associate to many benefits. However, problem arises when someone’s lovely pet had lost, illness, injury, or facing death. As a consequence, the owner has facing a hard time to find out and track cat’s last location. Also, monitoring cat’s health condition from time to time need a certain expertise. Therefore, the purpose of this product development is to monitor health status by indicating body temperature, and track his location. The prototype was developed based on the design thinking model; Empathize, Define, Ideate, Prototype and Test phases. The prototype circuit consists of the module for GPS detector and temperature detector. GPS will display the location of the pet's presence on the Google Map and the cat's body temperature readings will display after upon request. Testing indicates the prototype works according to flow. Thus, it can satisfy the purpose of this project to ease the pet’s owner.